2004
DOI: 10.1123/ijsnem.14.6.647
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pre-Exercise High Carbohydrate Meals with Different Glycemic Indices on Blood Leukocyte Redistribution, IL-6, and Hormonal Responses during a Subsequent Prolonged Exercise

Abstract: The purpose of this study was to determine the effect of pre-exercise high carbohydrate meals with high glycemic index (HGI) or low glycemic index (LGI) on blood leukocyte redistribution during subsequent endurance exercise. Eight male subjects performed a 90-min run on a treadmill at 70 % VO2max 3 h after ingesting an isocaloric HGI or LGI meal with GI values of 77 and 37, respectively. Blood counts of leukocytes, and neutrophils and the neutrophil/lymphocyte ratio were significantly lower in LGI than HGI at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…Consistent with this, IL-6 induces lipolysis in 3T3-LI adipocytes and increases fat oxidation in myotubes and in isolated rat soleus muscle [197]. In addition, it has been suggested that IL-6 influences glucose homeostasis during exercise [198][199][200]. In the latter study, young men performed a bicycle exercise at three separate occasions, at a relative high intensity or at a low intensity, with or without an infusion of recombinant (r)IL-6, which matched the circulating concentration of IL-6 in the high-intensity trial.…”
Section: Is the Muscle Il-6 Release A Metabolic-related Event?supporting
confidence: 55%
See 1 more Smart Citation
“…Consistent with this, IL-6 induces lipolysis in 3T3-LI adipocytes and increases fat oxidation in myotubes and in isolated rat soleus muscle [197]. In addition, it has been suggested that IL-6 influences glucose homeostasis during exercise [198][199][200]. In the latter study, young men performed a bicycle exercise at three separate occasions, at a relative high intensity or at a low intensity, with or without an infusion of recombinant (r)IL-6, which matched the circulating concentration of IL-6 in the high-intensity trial.…”
Section: Is the Muscle Il-6 Release A Metabolic-related Event?supporting
confidence: 55%
“…Adding to what we knew about this topic, recently a number of studies have clearly demonstrated that glucose ingestion during exercise attenuates the exercise-induced increase in plasma-IL-6 [195,[197][198][199][200]. This effect has been demonstrated for different types of training, for example running or cycling [199,200].…”
Section: Is the Muscle Il-6 Release A Metabolic-related Event?mentioning
confidence: 99%
“…European Journal of Clinical Investigation Vol 47 601 plasma IL-6 [29,[41][42][43][44][45][46][47][48][49][50]. Taken together, the systemic IL-6 response to exercise is dependent on the duration and intensity of exercise, the muscle mass engaged during exercise, the muscular glycogen level and whether or not carbohydrate is ingested during the exercise, whereas the mode of exercise has little impact.…”
Section: Anti-inflammatory Effects Of Acute Exercisementioning
confidence: 99%
“…The influence on some immune variables of a CHO containing meal with different glycemic indices (GI) and glycemic loads (GL) ingested 2–3 h before endurance exercise was also tested [59,60,61]. It was found that a pre-exercise meal with a high CHO amount (65% of energy intake) may attenuate exercise-induced cytokine response, and influences leukocyte trafficking [59].…”
Section: Nutritional Modulation Of Exercise-induced Immunodepressionmentioning
confidence: 99%
“…It was found that a pre-exercise meal with a high CHO amount (65% of energy intake) may attenuate exercise-induced cytokine response, and influences leukocyte trafficking [59]. The influence of pre-exercise meals consisting of low GI foods on exercise-induced cortisol and cytokine response compared to high GI meals remains still unclear because results are inconsistent [60,61]. …”
Section: Nutritional Modulation Of Exercise-induced Immunodepressionmentioning
confidence: 99%